Diagram of Bendix Mass Spectrometer - Bendix Corporation (1970)
Schematic diagram of a section of a Bendix Time-of-Flight Mass Spectrometer, with view of the oscilloscope, ion source, drift path, and electron multiplier. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Mass spectrometers